MODEL SUPERVISI PEMBELAJARAN MOLIT’O PAUD - Modjo, Usman (JIV-Jurnal Ilmiah Visi, 2018)
Supervision is seen as important to be developed after taking into account the facts, problems, and stakeholders of PAUD in the exploration study in May 2017. The Moleconomic Instructional Supervision Model aims to (1) solve the problems faced by PAUD educators regarding PAUD education standards, (2) concepts that underlie the supervision of Moliti’O instructional become one of the problems faced by PAUD educators regarding PAUD education standards, and (3) Finding a model of supervision of Moliti’O instructional that can foster the imagination of learners. The results of the discussion show a model of supervision of instructional needs to consider the characteristics of the subject studied. Early-age children who are still in the preoperational stage require a model of instructional supervision that can foster the imagination within the learners as well as the deepening of a model of supervision of instructional Moliti’O as well as guidelines for supervision of instructional Moliti’O. References Arikunto, S. (2006). Dasar-dasar supervisi. Jakarta: PT Rineka Cipta. Mulyasa, E. (2007). Menjadi kepala sekolah profesional. Bandung: Remaja Rosdakarya. Prasojo, D.L. & Sudiyono. (2011). Supervisi pendidikan. Bandung: Remaja Rosdakarya. Purwanto, N. (2005). Administrasi dan supervisi pendidikan. Bandung: Remaja Rosdakarya. Pusat Pengembangan Tenaga Kependidikan. (2014). Supervisi akademik implementasi kurikulum 2013. Jakarta: Kemdikbud. Sahertian, A.P. (2008). Konsep dasar dan teknik supervisi pendidikan. Jakarta: Rineka Cipta. Sudjana, N., dkk. (2011). Buku kerja pengawas sekolah. Jakarta: Pusat Pengembangan Tenaga Kependidikan, Badan PSDM dan PMP Kemendiknas.